ANALISIS KEPUASAN PELAYANAN BAGI PELANGGAN DI OBYEK WISATA TAMAN MARGA SATWA MANGKANG - Susilo, Agus; Suryaningsih, Margaretha; Lestari, Hesti (Journal of Public Policy and Management Review, 2013)
This research aims is to describe the level of service satisfaction forcustomers in the State Highways Animal Sights Mangkang. The study used adescriptive quantitative research or design that is mixed between qualitative withquantitative to measure customer satisfaction in service for Marga Park AnimalSights Mangkang. The sample of this study is 150 respondents. Data analysistechnique uses the Community Satisfaction Index.The findings of the research show that the overall performance quality ofservice to customers in the State Highways Animal Sights Mangkang becategorized either. However, some aspects still need to be repaired, althoughsome other aspects have shown good performance.Some aspects of the performance are good, they are: Disclosure ofinformation about service procedures, clarity of line role in the procedure ofservice, simplicity of procedures, identity assurance, and responsibilities of careworkers, workers in providing service Honesty, Courtesy and friendliness ofservice personnel, Respect and appreciation officer with the public, details ofservice charges Clarity, Clarity service schedule.Then the other aspects that still need to be improved performance include:easy to find / contact the service personnel, certainty responsible of ministryofficials, Reliability schedule service, cleanliness and neatness of theenvironment, availability of service facilities, modern and completeness offacilities and infrastructure, security neighborhood services, security facilitiesand services are used, the security against risks resulting from the implementationof the service.